Conceptual Understanding of Brimhana karma - Manjula; Sudipt Rath; Mita Kotecha (Journal of Ayurveda)
Objective:In the present-day world, the emergence of various debilitating diseases as well as medical treatments is rendering people to be weak and emaciated, hence pointing at the necessity to understand Brimhana karma of Ayurveda which may be equated with mass and weight promoters and is one of the Dvividhopa karma. Data Source:Ayurveda classics, viz., Caraka, Sushruta, Ashtanga Hridaya, Ashtangasangraha, Rasa Vaisesika Sutra, Dravyaguṇa siddhanta, and their commentaries, Research articles. Review Methods:Collected data were utilized and analyzed to understand the action of Brimhana karma and draw meaningful conclusions. Result and Conclusion:Brimhana undisputedly enhances Mamsa dhatu by enhancing stability through nourishment, which in turn enhances the Bala too, as physical strength depends on muscle strength. Further, both Bala and Brimhana are comparable to ojas. Dalhana explains the mode of action by means of predominance of Svabala-utkarsha, i.e., Dravya prabhava; Svaguna-utkarsha, i.e., predominance of either Rasa, Guna, Virya, or Vipaka; or predominance of both at a time which is equivalent to mode of action of Aushadha dravya in general. Rasa Vaisheshika credits the “Panchalakshana of Dravya”. Brimhana karma increases Shleshma and subsides Vata which is just opposite to Shleshma. Pharmacodynamical properties of Brimhana dravya along with factors responsible for Sharira vriddhi, viz. Kala Yoga, Svabhava, Avighata, and Ahara saushthava, may be manipulated or effectively utilized to assist in Brimhana karma.